Criminal Acts of Adultery Based on Islamic Law and Positive Law in Indonesia - Syafaatullah, M. Rafli; Zulfiko, Riki (al-Rasῑkh: Jurnal Hukum Islam, 2025)
Adultery is a complex social phenomenon that raises various moral, social, and legal issues in Indonesia. The existence of positive legal regulations and sanctions within Islamic law shows different approaches in addressing this problem; however, their effectiveness still requires comprehensive analysis. This study aims to compare the concepts, sanctions, and enforcement mechanisms regarding adultery according to Islamic law and positive law in Indonesia. The method used is normative research with literature analysis of laws and regulations, fiqh texts, and legal literature from both national and Islamic perspectives. The results indicate that the application of sanctions under Islamic law, such as stoning and flogging, has a more effective preventive and curative impact in combating adultery compared to lighter criminal sanctions under positive law, which is based on delik aduan (complaint-based offenses). Enforcement of Islamic law is also more effective and efficient because it is grounded in a strict system of evidence that does not rely on third-party advocacy, unlike the subjective and limited nature of positive law systems. The contribution of this research is to provide guidance for developing a more just and humane criminal law policy, as well as integrating sharia values into Indonesia’s legal reforms.